2012
DOI: 10.1002/lary.23738
|View full text |Cite
|
Sign up to set email alerts
|

Gastroesophageal reflux evaluation in patients affected by chronic cough: Restech versus multichannel intraluminal impedance/pH metry

Abstract: OP pH metry detected less reflux episodes than MII/pH; 35% of the OP events were swallows according to impedance. Time correlation between cough and reflux could not be demonstrated with OP pH metry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 21 publications
3
31
1
2
Order By: Relevance
“…In a recently published study, we were able to demonstrate that a pathological acidic environment in the oropharynx in LPR-patients was not correlated to objectified gastroesophageal reflux episodes [9] . These results were reconfirmed in another study with the same design [10] . Based on these data, the generally accepted pathomechanism of the direct alteration of the laryngeal epithelium by gastric contents, resulting in LPR-symptoms, needs to be reconsidered and alternative mechanisms should be discussed.…”
Section: Introductionsupporting
confidence: 54%
See 3 more Smart Citations
“…In a recently published study, we were able to demonstrate that a pathological acidic environment in the oropharynx in LPR-patients was not correlated to objectified gastroesophageal reflux episodes [9] . These results were reconfirmed in another study with the same design [10] . Based on these data, the generally accepted pathomechanism of the direct alteration of the laryngeal epithelium by gastric contents, resulting in LPR-symptoms, needs to be reconsidered and alternative mechanisms should be discussed.…”
Section: Introductionsupporting
confidence: 54%
“…As reported in previous trials, Dx-pH more often detects pathological acid pH levels than the standard pH/MII. On the other hand, the pharyngeal system regularly misses proximal pH exposure that is documented in regular pH/MII [9,10] . Hence, the clinical significance of this Dx-pH system is not clear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vailati et al [113] showed the high specificity and reasonable sensitivity of the Restech technique, which could be considered an interesting tool that can be used before therapy in patients with pharyngoesophageal reflux. In contrast, Ummarino et al [114] did not show any correlation, although chronic coughing was the only symptom reported by patients, and when they compared MII-pH and Restech, the superiority of the first technique seemed clear. Similarly, Becker et al [115] evaluated, in a prospective, single-center trial, the differences between MII-pH and Dx-pH.…”
Section: Dx-ph (Restech)mentioning
confidence: 82%